Functional and mechanical properties of mango peel pectin-based edible film - Cardinez, Ma. Cecilia C.
Agro-industrial wastes from the mango industry in the Philippines such as mango peels can be a source of pectin which can be used in the production of edible films. In this study, pectins from mango peel, apple, and citrus were characterized (in terms of degree of esterification, methodoxyl content, and galacturonic acid content) and were made into edible films. The physical, functional and mechanical properties (color, opacity, thickness strength, water vapor permeability, and water solubility) of the films were determined and compared with commercially available hot casing to evaluate their potential application in meat products. Results showed that mango peel pectin-based and apple pectin-based films have similar thickness, tensile strength, water vapor permeability, and water solubility, and only differ in color and opacity. Mango peel pectin-based edible film also exhibited parallel performance with hog casing in thickness, tensile strength, and water vapor permeability. However, the pectin-based edible films significantly deviated (p<0.05) from hog casing in terms of water solubility, with the pectin-based edible films being more water soluble. It is concluded that mango peel pectin based edible film could be utilized as packaging for meat products such as sausages provided that its properties are further improved. It is recommended that a reformulation of the film forming solution is done by adjusting the concentrations of glycerol and calcium chlolride. Application of the edible film on meat products to further establish its potential use is aslo recommended.